Obsessive-compulsive symptoms among the general population during the first COVID-19 epidemic wave in Italy - Pacitti, Francesca; Socci, Valentina; D'Aurizio, Giulia; Jannini, Tommaso Benedetto; Rossi, Alessandro; Siracusano, Alberto; Rossi, Rodolfo; Di Lorenzo, Giorgio (Journal of psychiatric research, 2022)
This study investigated obsessive-compulsive symptoms (OCS) in the Italian general population during the initial stage of the pandemic and the impact of COVID-19 related potential risk factors. A web-based survey was spread throughout the internet between March 27th and April 9th, 2020. Twenty thousand two hundred forty-one individuals completed the questionnaire, 80.6% women. The Dimensional Obsessive-Compulsive Scale (DOCS) was included to assess the severity of the obsessive-compulsive symptom domains. Further, selected outcomes were depression, anxiety, insomnia, perceived stress, and COVID-19 related stressful life events. A panel of logistic or linear regression analyses was conducted to explore the impact of COVID-19 related risk factors, socio-demographic variables, and mental health outcomes on OCS. A total of 7879 subjects (38,9%) reported clinically relevant OCS. Specifically, more than half of the sample (52%) reported clinically relevant symptoms in the Contamination domain, 32.5% in the Responsibility domain, 29.9% in the Unacceptable thoughts domain, and 28.6 in the Symmetry/Ordering domain. Being a woman was associated with OCS, except for Symmetry/Ordering symptoms. A lower education level and younger age were associated with OCS. Moreover, depression, anxiety, perceived stress symptoms, insomnia, and different COVID-19 related stressful events were associated with OCS. We found high rates of OCS, particularly in the contamination domain, in the Italian general population exposed to the first COVID-19 epidemic wave and COVID-19 related risk factors. These findings suggest the need to investigate further the trajectories of OCS in the general population along with the long-term socio-economic impact of the pandemic.